Applications of the deferred generalized de la Vall´ee Poussin means in approximation of continuous functions - KRASNIQI, Xhevat Z. (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
In this paper we have proved a theorem which show the degree of approximation of periodic functions by some generalized means of their Fourier series. In addition, our result is extended to two-dimensional setting as well. Mathematics Subject Classification (2010): 42A10, 42A16. Received 02 January 2020; Accepted 25 May 2020.